Information quality in e-health 7th Conference of the Workgroup Human-Computer Interaction and Usability Engineering of the Austrian Computer Society, USAB 2011, Graz, Austria, November 25-26, 2011, proceedings - Holzinger, Andreas; Simonic, Klaus-Martin (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 7th Conference of the Workgroup Human-Computer Interaction and Usability Engineering of the Austrian Computer Society, USAB 2011, in Graz, Austria, in November 2011. The 18 revised full papers together with 29 revised short papers and 2 posters presented were carefully reviewed and selected from 103 submissions. The papers are organized in topical sections on cognitive approaches to clinical data management for decision support, human-computer interaction and knowledge discovery in databases (hci-kdd), information usability and clinical workflows, education and patient empowerment, patient empowerment and health services, information visualization, knowledge & analytics, information usability and accessibility, governmental health services & clinical routine, information retrieval and knowledge discovery, decision making support & technology acceptance, information retrieval, privacy & clinical routine, usability and accessibility methodologies, information usability and knowledge discovery, human-centred computing, and biomedical informatics in health professional education.